Epidemiology, Pathogenesis, and Prevention of Head and Neck Cancer - Olshan, Andrew F.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Epidemiology, Pathogenesis, and Prevention of Head and Neck Cancer provides a current perspective on the epidemiology of head and neck cancer. Cancers of the oral cavity, pharynx, and larynx comprise an important group of tumors with diverse international patterns of incidence and mortality, established associations with tobacco and alcohol use, the human papilloma virus, and potential determinants of genetic susceptibility. Because of these factors, head and neck cancer offers a unique insight into mechanisms of cancer initiation and progression and gene-exposure interaction. This book brings together the latest epidemiologic and molecular genetic evidence regarding the patterns of occurrence and causes of head and neck cancer. In addition, Epidemiology, Pathogenesis, and Prevention of Head and Neck Cancer considers approaches to chemoprevention, and incorporates a multidisciplinary perspective including salient clinical, pathologic, molecular, and epidemiologic contributions.
Classification, Clinical Features, and Molecular Genetic Models -- Descriptive Epidemiology: U.S. Patterns -- Descriptive Epidemiology: International Patterns -- Risk Factors: Tobacco and Alcohol -- Human Papillomavirus and Head and Neck Cancer -- Dietary Factors -- Occupation and Other Risk Factors for Head and Neck Cancer -- Host Susceptibility and Molecular Epidemiology -- Chemoprevention of Head and Neck Cancers.
Keywords: Medicine; Oncology; Toxicology; Biomedicine; Cancer Research; Pharmacology/Toxicology.